1995
DOI: 10.1111/j.1365-2362.1995.tb01950.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms underlying the increased duodenal iron absorption in rats in response to phenylhydrazine‐induced haemolytic anaemia

Abstract: Haemolytic anaemia induced by phenylhydrazine (PZ) promotes iron absorption across rat small intestine. This present study investigates the role of the brush border potential difference (Vm) and mucosal reducing activity in the response. In addition, quantitative autoradiography was used to assess PZ-induced changes in the villus localization of brush border iron uptake. Iron transfer from duodenum to blood was increased significantly 5 days after treatment with PZ. Autoradiography showed that most brush borde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 22 publications
5
33
0
Order By: Relevance
“…Hepcidin expression has been shown to be suppressed on day 3 after PHZ administration in order to promote iron absorption [19,20]. In present study, we found that the hepcidin mRNA levels were gradually reduced in over the time course, almost up to 8-fold on day 5, a then was ameliorated compared to the untreated control ( Fig.…”
Section: Enhanced Erfe Expression Controls Iron Mobilization Under Phsupporting
confidence: 54%
See 3 more Smart Citations
“…Hepcidin expression has been shown to be suppressed on day 3 after PHZ administration in order to promote iron absorption [19,20]. In present study, we found that the hepcidin mRNA levels were gradually reduced in over the time course, almost up to 8-fold on day 5, a then was ameliorated compared to the untreated control ( Fig.…”
Section: Enhanced Erfe Expression Controls Iron Mobilization Under Phsupporting
confidence: 54%
“…1C, P b 0.05). By contrast, consistent with reduced RBC content, the percentage of R6 cells was also significantly decreased in PHZ-treated group at 40 mg/kg and 80 mg/kg, compared with the control group (4.41% and 3.2% vs. 5.57%) ( Previous studies have suggested that PHZ-induced hemolytic anemia could promote iron absorption in duodenum of experimental animals [19,20]. In the current study, we found that serum heme and non-heme iron levels were significantly increased in mice with PHZ administration at 40 mg/kg (2-fold and 3-fold) and 80 mg/kg (2.5-fold and 7-fold) compared to control (Fig.…”
Section: Establishment Of Hemolytic Anemia Mouse Modelmentioning
confidence: 56%
See 2 more Smart Citations
“…Studies in which rats were treated with an iron-deficient diet have shown that this treatment results in similar duodenal changes. [1][2][3] A mechanistic study in mice also established increased proliferation of the epithelium of duodenal mucosa after 4 weeks at the carcinogenic dose of 2000 ppm, demonstrating that the same mechanism occurs in this species.…”
Section: Mechanistic Studies On Carcinogenic Effectsmentioning
confidence: 92%